Effectiveness of Levels of Health Education on HbA1c in Al-Qassim Region, Saudi Arabia - Alnohair, Sultan Fahad (International Journal of Health Sciences, 2013)
<!--[if gte mso 9]> <![endif]--> Objective: The aim of this study is to assess the effect of different levels of health education on diabetes outcome among patients visiting the Primary Health Care (PHC) Centers in Al-Qassim Region. Methods: This study was conducted between October 2012 and March2013. Baseline HbA1C results recorded for all those included in the study, After 6 months of health education a well-constructed questionnaire for each other diabetic patient (male or female) visiting the PHC Center, last reading for HbA1c for each patient recorded.. The majority of the health education services included in this study was related to diabetes. Sample size calculated and increased to 420 to account for the design effect. Data entry and analysis was carried out using SPSS (version 17 for Windows. Results: Male respondent to a self-administered questionnaire is 70.1 %. Our study revealed that more exposure to all levels of health education will result in more to control diabetes compare to one or two types of health education. HbA1c level improved after health education. Conclusion: Improving the communication skills and health awareness among service providers in in PHC Centers through well designed programs involving health educators will improve the outcome among patients with diabetes mellitus and population in general. Moreover, medical students should be involved in such activities of health education in the community related health problems. Key words: Key words: Levels of health education; Diabetes Mellitus; HbA1c <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->